Effect of brewery waste on nutrient digestability of paddy straw based diet in lactating cows - S SenthilKumar (Department of Animal Nutrition, College of Veterinary and Animal Sciences, 2009)
Two experiments were conducted, one to assess the effect of brewery waste on nutrient digestibility of paddy straw based diet in lactating cows and the other to study the in vitro disappearance, degradability and rumen fermentation characteristics of various experimental feeds in Rumen Simulation Technique (RUSITEC). In animal study, eighteen early lactating cross bred cows within 20 days of lactation were selected and grouped into three as uniform as possible with regard to their age, body weight, parity, previous milk yield and stage of lactation. They were randomly allotted to the three dietary treatments T1, T2 and T3. The control concentrate mixture and paddy straw formed the T1 ration. The animals of T2 and T3 were fed with experimental concentrate mixture containing 25 per cent brewery waste (on DM basis) and paddy straw as roughage. In T2, the brewery waste was fed separately on wet basis, while in T3, the brewery waste to be incorporated in the concentrate mixture was treated with required quantity of paddy straw, three days before feeding. A feeding trial was carried out for a period of 60 days. There was no significant difference (P>0.05) in body weight and average daily dry matter intake (DMI) of experimental animals among the treatment groups T1, T2 and T3. The animals maintained on the three dietary treatments T1, T2 and T3 showed an average daily milk production of 8.03, 10.14 and 11.09 kg, respectively during the 60 day period of the experiment. The milk production was significantly increased (P<0.05) from fourth week onwards in brewery waste fed groups (T2 and T3) when compared with control (T1). The cost of feed per kg milk produced was lower in animals maintained on T2 and T3 rations (Rs. 7.89 and 8.37, respectively) than those fed control ration (Rs. 10.40).